2012
DOI: 10.1007/s10681-012-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of main and epistatic effects for flour color traits in durum wheat

Abstract: The aim of this work was to map quantitative trait loci (QTLs) associated with flour yellow color (Fb*) and yellow pigment content (YPC) in durum wheat (Triticum turgidum L. var. durum). Additionally, QTLs affecting flour redness (Fa*) and brightness (FL*) color parameters were investigated. A population of 93 RILs (UC1113 9 Kofa) was evaluated in three locations of Argentina over 2 years. High heritability values ([94%) were obtained for Fb* and YPC, whereas FL* and Fa* showed intermediate to high values. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 39 publications
8
53
0
1
Order By: Relevance
“…The QTLs that mapped to chromosomes 7A (Mares and Campbell 2001;Patil et al 2008;Zhang et al , 2009Howitt et al 2009;Blanco et al 2011) and 7B (Kuchel et al 2006;Pozniak et al 2007; have been shown to explain in many cases the highest percentages of observed phenotypic variability (>50%) (Parker et al 1998;Elouafi et al 2001). Recent findings have shown that as well as the QTLs mapped at the telomeric region of the long arms of these chromosomes, there are other QTLs that have minor effects on colour traits on both arms of chromosomes 7A (Singh et al 2009;Blanco et al 2011;Roncallo et al 2012) and 7B Blanco et al 2011;Roncallo et al 2012).…”
Section: Genetic Control Of Carotenoid Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The QTLs that mapped to chromosomes 7A (Mares and Campbell 2001;Patil et al 2008;Zhang et al , 2009Howitt et al 2009;Blanco et al 2011) and 7B (Kuchel et al 2006;Pozniak et al 2007; have been shown to explain in many cases the highest percentages of observed phenotypic variability (>50%) (Parker et al 1998;Elouafi et al 2001). Recent findings have shown that as well as the QTLs mapped at the telomeric region of the long arms of these chromosomes, there are other QTLs that have minor effects on colour traits on both arms of chromosomes 7A (Singh et al 2009;Blanco et al 2011;Roncallo et al 2012) and 7B Blanco et al 2011;Roncallo et al 2012).…”
Section: Genetic Control Of Carotenoid Biosynthesismentioning
confidence: 99%
“…Significant marker-trait associations for YPC have been detected on all of the chromosomes by linkage mapping (Parker et al 1998;Hessler et al 2002;Pozniak et al 2007;Patil et al 2008;Zhang et al , 2009Howitt et al 2009;Blanco et al 2011;Roncallo et al 2012) and by association mapping (Reimer et al 2008).…”
Section: Genetic Control Of Carotenoid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Major QTL associated with the color of flour have been found on all chromosome arms using recombinant inbred lines, DH populations and the genetic resources of common wheat (Triticum aestivum L.) (Mares & Campbell, 2001;Kuchel et al, 2006;Zhang et al, 2009aZhang et al, , 2009bSadeque & Turner, 2010a;Bordes et al, 2011;Li et al, 2011;Tsilo et al, 2011;Roncallo et al, 2012;Zhao et al, 2013). The QTL for yellow pigments, polyphenol oxidase and carotenoid genes were also found to be associated with the flour and noodle color (Marles & Campbell, 2001;Raman et al, 2007;He et al, 2008;Zhang et al, 2009b;Sadeque & Turner, 2010b;Crawford et al, 2011;Martin et al, 2011;Crawford & Francki, 2013a, 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of a large number of genetic resources is essential for this procedure. To date, significant progress in identifying QTLs conferring yield components, grain qualities, and disease resistance in durum wheat varieties has been achieved (Zhang et al, 2008;Simons et al, 2011;Roncallo et al, 2012). The wild germplasm of durum wheat, which represents a rich potential source of useful under-exploited genes, has also been used as a resource to provide genes of interest.…”
Section: Introductionmentioning
confidence: 99%